2021
DOI: 10.3390/cells10040722
|View full text |Cite
|
Sign up to set email alerts
|

CXCL12-Abundant Reticular (CAR) Cells Direct Megakaryocyte Protrusions across the Bone Marrow Sinusoid Wall

Abstract: Megakaryocytes (MKs) release platelets into the lumen of bone marrow (BM) sinusoids while remaining to reside within the BM. The morphogenetic events of this complex process are still not fully understood. We combined confocal laser scanning microscopy with transmission and serial block-face scanning electron microscopy followed by 3D-reconstruction on mouse BM tissue sections. These analyses revealed that MKs in close vicinity to BM sinusoid (BMS) wall first induce the lateral retraction of CXCL12-abundant re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…CXCL12/SDF-1α, acting through CXCR4, can substantiate cell migration, proliferation, differentiation, and survival [ 15 , 16 , 46 , 47 , 48 , 49 ]. The CXCL12/SDF-1α gradient modulated by CXCR4 in the bone marrow vascular niche influences maturation of megakaryocytes, the formation of proplatelet extension and the release of platelets into the perfusing vessels, during platelet biogenesis, i.e., megakaryopoiesis ( Figure 1 ) [ 41 , 50 , 51 , 52 , 53 , 54 ]. The pronounced effect of CXCL12/SDF-1α-CXCR4 axis on megakaryopoiesis, especially migration of immature megakaryocytes, has been simultaneously demonstrated by several groups in culture derived megakaryocytes from CD34 + bone marrow and cord blood-derived human progenitor cells [ 41 , 50 , 51 , 52 , 53 ].…”
Section: The Dichotomy Of Cxcr4 and Ackr3/cxcr7 In Plateletsmentioning
confidence: 99%
See 1 more Smart Citation
“…CXCL12/SDF-1α, acting through CXCR4, can substantiate cell migration, proliferation, differentiation, and survival [ 15 , 16 , 46 , 47 , 48 , 49 ]. The CXCL12/SDF-1α gradient modulated by CXCR4 in the bone marrow vascular niche influences maturation of megakaryocytes, the formation of proplatelet extension and the release of platelets into the perfusing vessels, during platelet biogenesis, i.e., megakaryopoiesis ( Figure 1 ) [ 41 , 50 , 51 , 52 , 53 , 54 ]. The pronounced effect of CXCL12/SDF-1α-CXCR4 axis on megakaryopoiesis, especially migration of immature megakaryocytes, has been simultaneously demonstrated by several groups in culture derived megakaryocytes from CD34 + bone marrow and cord blood-derived human progenitor cells [ 41 , 50 , 51 , 52 , 53 ].…”
Section: The Dichotomy Of Cxcr4 and Ackr3/cxcr7 In Plateletsmentioning
confidence: 99%
“…Subsequent investigation from Rafii’s group demonstrated transmigration of CD34 + -derived mature polyploid megakaryocytes through a monolayer of bone marrow endothelial cells across a CXCL12/SDF-1α and their ability to generate functional platelets [ 53 ]. Only recently has the contribution of CXCL12/SDF-1α enriched bone marrow reticular cells been elegantly elaborated in megakryopoiesis and proplatelet production in the mouse bone marrow sinusoidal microenvironment [ 54 ]. Much like their parental cells, mature human platelets can transmigrate through the endothelium following a CXCL12/SDF-1α gradient sensed through CXCR4, which is inhibited by CXCR4 antagonist AMD3100, Gαi inhibitor pertussis toxin, PI3K inhibitors LY294002 or wortmannin, and by disrupting actin polymerization with cytochalasin B [ 55 , 56 ].…”
Section: The Dichotomy Of Cxcr4 and Ackr3/cxcr7 In Plateletsmentioning
confidence: 99%
“…Human blood cells are produced in the extravascular space of the BM, and to enter the circulation, blood cells must migrate to the barrier between the hematopoietic compartment and the circulation, the MBB [ 1 ]. Several observations have demonstrated that MBB regulates cell trafficking by retaining immature or defective cells while permitting the passage of suitable cells [ 1 , 2 ]. Different blood cells migrate in different ways.…”
Section: Introductionmentioning
confidence: 99%
“…Platelet biogenesis is a complex cellular process, 1,2 initiated by mature MKs in direct contact with the BM sinusoids, 3 and involves the penetration of endothelial cells, 4,5 and the extension of large cytoplasmic protrusions into the sinusoidal lumen, 6,7 which are shed and undergo maturation in the peripheral circulation to become bona fide platelets. The different steps of platelet biogenesis highly depend on rearrangements of both the microtubule (MT) and actin cytoskeletal network.…”
Section: Introductionmentioning
confidence: 99%